Resilience factors, pain, and physical activity in adolescent chronic musculoskeletal pain: Design and protocol of a pilot phase 2 single-group, non-randomized clinical trial - Faith Logan; Madeline Marsh; Adam Hively; Jacqueline Warner; Ann Davis; Jamie L. Jackson; William Black (PLoS ONE, 2026)
Introduction Chronic musculoskeletal pain (CMSKP) in adolescence is associated with physical, psychological, social, and academic impairment and increased risk for chronic pain in adulthood. Although physical activity interventions are an evidence-based approach for managing pediatric chronic pain, many adolescents with CMSKP avoid physical activity due to fear of increased pain, low confidence in physical functioning, and other pain-avoidance behaviors. Resilience-focused interventions targeting self-efficacy, motivation, and mental flexibility may improve engagement in valued activities despite pain. This study describes the design and protocol of the Pain REsilience Promotion for Youth (PREP-Y) intervention, a resilience-focused physical activity intervention for adolescents with CMSKP. Methods and analysis This single-site, pilot phase 2, single-group, non-randomized clinical trial will enroll 40 adolescents aged 12–17 years with CMSKP from Nationwide Children’s Hospital in Columbus, Ohio, USA. Participants complete questionnaires, objective physical functioning assessments, and physical activity monitoring using activPAL devices as baseline measures. Participants then complete 4 virtual resilience-focused intervention sessions targeting pain resilience, self-efficacy, motivation, and adaptive coping related to physical activity. Garmin watches are used to track activity during the intervention period. Follow-up assessments occur post-intervention and at 3 months post-intervention. Primary outcomes include feasibility and acceptability, assessed through recruitment, retention, attendance, intervention fidelity, and completion of study measures. Exploratory outcomes include physical activity, sedentary behavior, pain-related functioning, pain catastrophizing, kinesiophobia, self-efficacy, and resilience-related constructs. Ethics and dissemination The study was approved by the Nationwide Children’s Hospital Institutional Review Board. Findings will inform a future randomized clinical trial. This manuscript reflects protocol version 5.0 dated 23 March 2026. Trial registration ClinicalTrials.gov NCT06923891 .